Acute physical activity and sports injuries in children - Collard, D. C. M.; Verhagen, E. A. L. M.; Chin A Paw, M. J. M.; van Mechelen, W. (Applied Physiology, Nutrition, and Metabolism, 2008)
An increase in the physical activity of individuals has many health benefits, but a drawback of an increase in physical activity is the risk of related injuries. To reduce the short- and long-term effects in terms of social and economic consequences, prevention of physical activity injuries is an important challenge. A sequence of prevention model has been proposed that aims to prevent physical activity injuries in different steps. The model includes (i) identification of the problem in terms of incidence and severity of physical activity injuries, (ii) identification of the risk factors and injury mechanisms that play a role in the occurrence of physical activity injuries, (iii) introduction of measures that are likely to reduce the future risk and (or) severity of physical activity injuries, and (iv) evaluation of the effectiveness of the measures by conducting a randomized controlled trial (RCT). This review describes what is currently known about all of the various aspects of the sequence of prevention in children (steps i-iv).